Is there a role for surgical resection in patients with pancreatic cancer with liver metastases responding to chemotherapy?. Issue 10 (October 2016) - Crippa, S.; Bittoni, A.; Sebastiani, E.; Partelli, S.; Zanon, S.; Lanese, A.; Andrikou, K.; Muffatti, F.; Balzano, G.; Reni, M.; Cascinu, S.; Falconi, M.
Abstract: Background: New chemotherapeutic regimens have improved survival for stage IV pancreatic ductal adenocarcinoma and occasionally major response of liver metastases can be observed. Aim of this work is to analyze the outcomes of patients undergoing primary chemotherapy for liver metastases from pancreatic cancer and to evaluate the results of surgical resection. Methods: Retrospective analysis. Exclusion criteria: patients with extra-hepatic metastases, patients with Eastern Cooperative Oncology Group performance status ≥3, patients undergoing supportive care alone. Results: 127 patients were identified. Liver metastases were unilobar in 28.5% of patients. Chemotherapy regimens included gemcitabine alone or in association with other agents (44%), oxaliplatin, irinotecan, fluorouracil and leucovorin (FOLFIRINOX 8%), and cisplatin, gemcitabine plus capecitabine and epirubicin (PEXG) or capecitabine and docetaxel (PDXG) or epirubicin and fluorouracil (PEFG) (48%). 56 patients (44%) had a complete (7%) or partial response (37%). surgical resection was carried out in 11 patients (8.5%). Median overall survival was 11 months for the entire cohort and 15 months for those with partial/complete response. In this sub-group median survival was significantly longer (46 versus 11 months) for patients undergoing resection (P < 0.0001). Independent predictors of overall survival were chemotherapy with multiple agents (HR: 0.512), surgical resection (HR: 0.360), >5 liver metastases at diagnosis (HR: 3.515), and CA 19.9 reduction < 50% of baseline value (HR: 2.708). Conclusions: Surgical resection of primary pancreatic tumor with or without residual liver disease can be considered in selected cases after primary chemotherapy and it is associated with improved survival.